Description about Depression With Psychological Well Being of Elderly in Krajan, Lateng, Banyuwangi - Ramandini, Rizky Candra; Mandagi, Ayik Mirayanti (Tadulako University, 2023)
Elderly is a period of entering the final stage in the span of human life and elderly is often to be a person’s golden age. Depression is a mental health problem that can be experienced by anyone, including the elderly. Psychological well-being which means that a person is able to live a good life which is a combination of good feelings and can work effectively. The adult population with mental health disorders such as anxiety and depression is 11.6% or 17.4 million of the 150 million adult population in Indonesia. In 2018 cases of depression in Indonesia were in the provinces of Central Sulawesi at 12.3%, Gorontalo at 10.3% and North Maluku at 9.7%. The purpose of this research is to identify description of depression with psychological well-beingof elderly in RT IV RW IV Krajan, Banyuwangi. In this study, the research population was the elderly living in RT IV RW IV Krajan, Lateng, Banyuwangi with the elderly age 60 years and over with the number of elderly as many as 30 people. The technique used in the research is purposive random sampling. Based on the research, it was obtained information that depression in the elderly with good category was obtained as many as 20 people or 66.7%. Depression in the elderly with sufficient category of 10 people or 33.3%. based on the studies, it can be seen that depression in the elderly in RT IV and RW IV shows a good category. Keywords: Elderly, Depression, Psychological Well Being